Actividades del proyecto PERMAMODEL durante la campaña antártica 2006-07 - Tome, David; Ramos, Miguel; Hidalgo, Miguel Angel; Vieira, Gonçalo; Neves, Mário; Trindade, Alexandre (Finisterra, 2009)
(sem entrada)